2019
DOI: 10.3791/58883
|View full text |Cite
|
Sign up to set email alerts
|

A Continuous-flow Photocatalytic Reactor for the Precisely Controlled Deposition of Metallic Nanoparticles

Abstract: In this work, a novel photocatalytic reactor for the pulsed and controlled excitation of the photocatalyst and the precise deposition of metallic nanoparticles is developed. Guidelines for the replication of the reactor and its operation are provided in detail. Three different composite systems (Pt/graphene, Pt/TiO 2 , and Au/TiO 2 ) with monodisperse and uniformly distributed particles are produced by this reactor, and the photodeposition mechanism, as well as the synthesis optimization strategy, are discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…Graphene oxide samples were prepared by using the modified Hummers method 15 with few modifications. The detailed procedure used for GO synthesis and reactor design was proposed in Reference 21 and the video article was provided in Reference 22. Two grams of graphite powder (>99%, Sigma‐Aldrich) were added to 100 mL of sulfuric acid (H 2 SO 4 , 98%, Sigma‐Aldrich) and the mixture was placed in an ice‐water bath.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Graphene oxide samples were prepared by using the modified Hummers method 15 with few modifications. The detailed procedure used for GO synthesis and reactor design was proposed in Reference 21 and the video article was provided in Reference 22. Two grams of graphite powder (>99%, Sigma‐Aldrich) were added to 100 mL of sulfuric acid (H 2 SO 4 , 98%, Sigma‐Aldrich) and the mixture was placed in an ice‐water bath.…”
Section: Methodsmentioning
confidence: 99%
“…Considering these toxic and difficult‐to‐handle chemicals, one would prefer to use more environmentally friendly chemicals such as glucose, fructose, sucrose, 20 and ascorbic acid 9 . In our recent studies, we investigated the effect of highly concentrated sodium hydroxide on the bandgap modulation of GO 21,22 . Due to the tunable electronic bandgap structure, the application of GO in photocatalytic applications 23 or as an electron acceptor in solar cells has been proposed 15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partially reduced graphene oxide, PRGO, could be referred to as modulated band gap GO that shows semiconducting properties. 34,41,44,45 The photocatalytic deposition of metals, M, on PRGO could be explained with the following steps: 46 adsorption of M X+ containing a complex on the surface; electron−hole separation by light illumination; stepwise reduction of M X+ to the M 0 state, and at the same time the oxidation of the second chemical, the hole scavenger; formation of the Mcryst (crystallites of M) by two possible pathways: agglomeration of the reduced atoms or reduction of the complexes on the surface of previously deposited nuclei. The light source and the types of hole scavengers are crucial factors in regulating these steps.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene could also be among novel support materials to be used in catalyst development. ,,,, The beneficial properties of GO as a promising support in PEMFCs’ catalyst layer, CL, have been studied and mentioned elsewhere. ,,, It was demonstrated that graphene has H 2 up-taking ability, which led to less mass transport resistance and better kinetics of hydrogen oxidation. It has been reported that a photocatalytic deposition could result in carbon/Pt composites with strong interaction between graphitic domains of carbon and Pt .…”
Section: Introductionmentioning
confidence: 99%